Effects of synbiotic supplement on LPS level in Thai smokers: A preliminary study - Pratummas, Parama; Sirisapsombat, Vachrintr; Phucharoen, Phuttharaksa; Nararatwanchai, Thamthiwat; Chaiyasut, Chaiyavat; Sirilun, Sasithorn; Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: The impacts of smoking on the intestinal microbiome piece and arranged assortment have been appeared in different arranged controlled and observational clinical trials in individuals. Synbiotics are utilized not fair for the progressed survival of beneﬁcial microorganisms included to food, however in expansion for the prompting of the duplication of speciﬁc nearby bacterial strains display within the gastrointestinal tract. Aims and Objective: This research proposes the impact of synbiotic supplement on gut-brain axis in Thai smokers in the realm of gut-related biochemical parameters and cognition. Materials and Methods: We directed a single gathering, pre-and post-test study; 20 patients lived in Mahasarakham, Fagerstrom Test for Nicotine Dependence at 4 or above, and no history of cerebrovascular diseases, brain and abdominal surgery, and not taking hormones or medications impacted brainwaves or utilizing antibiotics inside about fourteen days prior. Subjects were allocated to synbiotic supplement containing 3 kinds of prebiotics and 7 types of probiotics prior to sleep every day for about two months. Results:Results were estimated in gut-related biochemical parameters change and alternation in cognition. The present outcomes have indicated essentially decline in the scores of Fagerstrom Test for Nicotine Dependence and also the scores of craving for smoke after intervention. In additions, lipopolysaccharide (LPS) in plasma significantly decreased after the intervention. Conclusion: Further researches are obligatory to lead in finding a propensity to improve in gut-related biochemical parameter and cognition after admission of synbiotic supplement.